Analisis Kinerja Keuangan Pada Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) Provinsi Jawa Barat Tahun 2017-2020 - Kalingga Aulia Ningrum; Khozin Arief (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this study was to determine the financial performance of the National Population and Family Planning Agency (BKKBN) of West Java Province for the 2017-2020 period in terms of financial performance which is useful to assist in financial management in order to achieve its targets and overcome the same obstacles every year. This study uses a quantitative descriptive research method with financial ratios as a benchmark. The financial ratios used in this study are liquidity ratios, solvency ratios, effectiveness ratios, efficiency ratios, and growth ratios. The results of this final project indicate that the financial performance of the BKKBN of West Java Province is stated to be good in terms of the liquidity ratio and stated to be very good in terms of the solvency ratio. While the financial performance of the West Java Province BKKBN seen from the effectiveness and efficiency ratios is declared less effective and efficient. Judging from the growth ratio of financial performance, it can be stated that it experienced positive growth even though it was fluctuating.